Until August - García Márquez, Gabriel, 1927-2014 (Alfred A. Knopf ; Viking, an imprint of Penguin Books ; Replika press, 2024)
"Sitting alone beside the languorous blue waters of the lagoon, Ana Magdalena Bach contemplates the men at the hotel bar. She has been happily married for twenty-seven years and has no reason to escape the life she has made with her husband and children. And yet, every August, she travels by ferry here to the island where her mother is buried, and for one night takes a new lover. Across sultry Caribbean evenings full of salsa and boleros, lotharios and conmen, Ana journeys further each year into the hinterland of her desire and the fear hidden in her heart. Constantly surprising, joyously sensual, Until August is a profound meditation on freedom, regret, self-transformation, and the mysteries of love--an unexpected gift from one of the greatest writers the world has ever known."--